Effects of ABA on growth, leaf stomatal characteristics, and photosynthesis of Iris lactea seedlings under NaCl stress - TIAN Xiaoxia; MAO Peichun; ZHENG Mingli; YU Ting; MENG Lin (Xibei zhiwu xuebao)
[Objective] The effects of abscisic acid (ABA) on the growth, leaf stomatal characteristics, and photosynthesis of Iris lactea seedlings under severe salt stress were studied. We aim to screen the appropriate ABA concentration to enhance salt tolerance of I. lactea, and to provide a basis for the cultivation of I. lactea that is tolerant to severe saline stress. [Methods] Using ‘ML04’ and ‘ML35’ I. lactea seedlings as materials, the biomass, stomatal density, photosynthesis rate, and other indices under NaCl stress after ABA spraying were analyzed. [Results] Under NaCl stress, both I. lactea seedlings showed salt damage symptom, and the leaf damage of ‘ML35’ was more severe than ‘ML04’. Spraying of ABA increased salt tolerance of the two I. lactea seedlings, and ‘ML04’ was increased more than ‘ML35’. ABA increased the plant height and biomass by adjusting the stomatal morphology and spatial distribution pattern to optimize the gas exchange process, reducing the decrease of chlorophyll content, and enhancing its photosynthesis, etc. [Conclusion] The damage of ‘ML35’ was more severe than ‘ML04’ under salt stress. Spraying ABA could alleviate the growth of I. lactea seedlings under salt stress, and 2.5 μmol/L ABA had the best effect.